Handbook of Asian Finance - Chuen, David; Gregoriou, Greg (Academic Press, 2014)
Participants in Asian financial markets have witnessed the unprecedented growth and sophistication of their investments since the 1997 crisis. Handbook of Asian Finance: REITs, Trading, and Fund Performance analyzes the forces behind these growth rates. Insights into banking, fund performance, and the effects of trading technologies for practitioners to tax evasion, market manipulation, and corporate governance issues are all here, presented by expert scholars. Offering broader and deeper coverage than other handbooks, the Handbook of Asian Finance: REITs, Trading, and Fund Performance explains what is going on in Asia today. Presents the only micro- and market-related analysis of pan-Asian finance available today Explores the implications implicit in the expansion of sovereign funds and the growth of the hedge fund and real estate fund management industries Investigates the innovations in technology that have ushered in faster capital flow and larger trading volumes.